Safety of induced sputum collection in children hospitalized with severe or very severe pneumonia - DeLuca, AN; Hammitt, LL; Kim, J; Higdon, MM; Baggett, HC; Brooks, WA; Howie, SRC; Knoll, M; Kotloff, KL; Levine, OS; Madhi, SA; Murdoch, DR; et al. (Oxford University Press, 2017)
Background Induced sputum (IS) may provide diagnostic information about the etiology of pneumonia. The safety of this procedure across a heterogeneous population with severe pneumonia in low- and middle-income countries has not been described. Methods IS specimens were obtained as part a 7-country study of the etiology of severe and very severe pneumonia in hospitalized children <5 years of age. Rigorous clinical monitoring was done before, during, and after the procedure to record oxygen requirement, oxygen saturation, respiratory rate, consciousness level, and other evidence of clinical deterioration. Criteria for IS contraindications were predefined and serious adverse events (SAEs) were reported to ethics committees and a central safety monitor. Results A total of 4653 IS procedures were done among 3802 children. Thirteen SAEs were reported in relation to collection of IS, or 0.34% of children with at least 1 IS specimen collected (95% confidence interval, 0.15%–0.53%). A drop in oxygen saturation that required supplemental oxygen was the most common SAE. One child died after feeding was reinitiated 2 hours after undergoing sputum induction; this death was categorized as “possibly related” to the procedure. Conclusions The overall frequency of SAEs was very low, and the nature of most SAEs was manageable, demonstrating a lowrisk safety profile for IS collection even among severely ill children in low-income-country settings. Healthcare providers should monitor oxygen saturation and requirements during and after IS collection, and assess patients prior to reinitiating feeding after the IS procedure, to ensure patient safety.